MON-622 Rapid Improvement in Glycated Albumin Before Educational Admission Predicts Fair Glycemic Control One Year After the Discharge of Patients with Type 2 Diabetes Mellitus - Katsuragawa, Sho (J Endocr Soc, 2020)
Background and Aim: Glycated albumin (GA) reflects a short-term glycemic control (about 2 weeks) in comparison to glycated hemoglobin (HbA1c) which reflects a long-term glycemic control. Thus, if the dietary, exercise, or medication therapy before the educational admission is effective, a rapid improvement in GA can be observed. However, the impact of the improvement in GA on the subsequent glycemic control is not well understood. This retrospective study analyzed the association between the change of GA before educational admission and glycemic control one year after the discharge of patients with type 2 diabetes mellitus (T2DM). Method: We analyzed data from 114 T2DM patients who were admitted to our hospital from 2011 to 2016. The GA data within 30 days before admission and on the day of admission were available for all patients. The change of GA per day (ΔGA/day) was calculated as [(GA on admission) - (GA before admission)/number of days between the two measurements of GA]. Patients with renal dysfunction (eGFR < 30 mL/min/1.73 m(2)) or insulin deficiency [fasting C-peptide (CPR) < 0.5 ng/mL or two-hour postprandial CPR < 1.0 ng/mL] were excluded. Patients achieving an HbA1c of < 7.0 % at one year after discharge were defined as achievers, and the rest were defined as non-achievers. Multiple baseline factors including the ΔGA/day between the two groups were compared. Results: Of the 114 patients, 68 were achievers and 46 were non-achievers. GA significantly declined during before and just after the admission to hospital (median [interquartile range]: 26.0 [22.2 - 32.7] to 25.0 [21.4 - 29.8] %, p < 0.001). The range of the ΔGA/day was between -1.14 and 0.28, with a median value of -0.08 [-0.26 - 0.002]. The age, body mass index, and HbA1c levels at admission were not significantly different between the two groups. The increase in CPR after the glucagon loading test was higher in the achievers than in the non-achievers (1.85 [1.32 - 2.87] vs 1.21 [0.53 - 1.92] ng/ml, p = 0.004). The ΔGA/day was lower in the achievers than in the non-achievers (-0.14 [-0.39 - -0.006] vs -0.04 [-0.13 - 0.03], p = 0.002). A logistic regression analysis demonstrated that the ΔGA/day was the factor associated with achieving an HbA1c of < 7.0% at one year after discharge (Odds ratio: 0.037, 95 % confidence interval: 0.004 - 0.267, p < 0.001). In the receiver operating characteristic curve analysis, the ΔGA/day had an area under the curve of 0.67 in the achievement group and the cutoff value was set as -0.146 for predicting the achievement, with a sensitivity of 0.50 and a specificity of 0.85. Conclusion: Our results suggest that the change in GA before the educational admission can predict the glycemic control one year after the discharge of T2DM patients.